Visible-light-driven Photodegradation of Commercial Dyes by the Cooperation of Co-doped TiO2 Material - Noonuruk, Russameeruk; Wattanawikkam*, Chakkaphan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2019)
The Co-doped TiO2 photocatalysts with various contents of Co were fabricated by co-precipitation method combined with calcinations at 500°C. Two different dyes of rhodamine b and methylene blue were used to evaluate the photocatalytic performance of the prepared samples. The different concentration of Co has significant influence on structural, morphological, optical properties as well as photocatalytic activity of TiO2 catalyst. The XRD diffraction patterns of all samples exhibit the anatase phase. X-ray photoelectron spectroscopy technique was used to investigate the chemical state of prepared samples. The BET measurement shows larger specific surface area of doped samples than that of pure TiO2. The incorporation of Co ions into TiO2 results in the red-shift in photo-absorption of samples toward visible region. The photocatalytic activities on rhodamine b and methylene blue dyes degradation clearly show that the performance of photodegradation highly depends on the concentration of dopant contents and type of organic dyes. The Co-doped TiO2 sample with 3% of Co dopant concentration exhibited superior photodegradation rate under visible light illumination in both of rhodamine b and methylene blue dyes. The influences of dopant ions and concentration on physical properties, optical absorption and photocatalytic activity on TiO2 are also discussed. Keywords: Co-doped TiO2; Photocatalyst; co-precipitation method *Corresponding author: Tel.: +66838744045 E-mail: chakkaphan_w@rmutt.ac.th